P377 Impact of moderate-to-severe endoscopic disease criteria on endoscopic response, endoscopic remission, and deep remission in patients receiving ustekinumab or adalimumab in the SEAVUE study. (21st January 2022) - Allez, M; Lewis, J D; Hanauer, S B; Danese, S; Irving, P M; Gasink, C; Hoops, T; Izanec, J L; Ma, T; Loftus, E V; Scherl, E J; Panaccione, R; et al.
Abstract: Background: Entry criteria and outcome measures of Crohn's disease (CD) clinical trials have evolved. Patients are now required to have active inflammation on screening endoscopy, with some studies requiring moderate-severe SES-CD scores. Recent trials have endoscopic response as a co-primary endpoint and endoscopic remission (ER) and deep remission (DR) as major secondary endpoints. Pivotal CD maintenance studies typically examine only responders to induction. The SEAVUE study required ≥1 ulceration of any size (SES-CD≥3) at baseline and had a treat-through design. To examine the results in the context of these trial design characteristics, we evaluated endoscopic outcomes at wk52 in the subgroup of pts with moderate-severe baseline SES-CD scores in SEAVUE, as well as those who were in clinical response after induction. Methods: Biologic-naïve pts failing or intolerant to conventional therapy with CDAI≥220/≤450 and SES-CD≥3 were eligible. Pts were randomized, 1:1 to UST (~6mg/kg IV at wk0 then, 90mg SC q8w) or ADA (SC, 160mg at wk0, 80mg at wk2, then, 40mg q2w). Endoscopic outcomes were evaluated in all pts and the subgroup with moderate-severe endoscopic disease (baseline SES-CD≥6 for ileocolonic or colonic disease or SES-CD≥4 for isolated ileal disease). Endoscopic response was a ≥50% reduction from baseline in SES-CD, SES-CD≤3, or SES-CD=0 for pts with baseline SES-CD=3. ER was SES-CD≤3 or, 0 in pts with baseline SES-CD=3. DR was CDAI<150 and ER. Results: Endoscopic outcomes for the subgroup with moderate-severe endoscopic disease were similar to those of the full cohort of pts. In UST-treated pts, endoscopic response was achieved at wk52 in, 41.9% in the full cohort and, 43.1% in the moderate-severe subgroup (Table, 1). In ADA-treated pts, endoscopic responses were, 36.9% and, 35.4%, respectively. For pts who were in clinical response after induction (Table, 1), endoscopic response rates were, 48.2% in the full cohort and, 49.5% in the moderate-severe subgroup for UST and, 44.8% and, 43.1%, respectively, for ADA. ER and DR rates were generally similar between the full cohort and the moderate-severe subgroup (Table, 2; eg, ERs were UST, 28.5% and ADA, 30.7% in full cohort; UST, 27.1% and, 27.8% ADA in subgroup). ER and DR rates were, 3%-7% higher in induction responders compared with the full cohort. Of note, even among wk16 nonresponders, some pts attained endoscopic outcomes at wk52 (eg, endoscopic responses in wk16 nonresponders were UST, 21.4% and ADA 13.3%). Conclusion: In SEAVUE, both the UST and ADA treatment groups achieved high endoscopic response, ER, and DR rates at wk52. Results in pts with moderate-severe endoscopic disease were similar to those of the full cohort, but clinical responders after induction had higher rates than the full cohort.